Editorial - Blotevogel, Hans Heinirch; Wever, Egbert (ERDKUNDE, 1997)
The articles contained in this issue go back to the fifth Dutch-German Seminar on Economic Geography which was jointly organised by EGBERT WEVER, Utrecht, and HANS H . BLOTEVOGEL, Duisburg, and which took place in Mülheim/Ruhr in May 1996.